Os profetas da educação no século xx e a redenção do homem do terceiro milênio - Tanaka, Heiji (2001)
From the moment that speeches on Education began to be formulated in a more systematic way, their essence was always directly linked to the society of each era in question. These speeches were concerned with inserting individuals into the social and economic context, aiming at improving the living conditions of society according to the point of view with which it was observed by analysts. Thus, issues such as worker training, citizen participation in public life, community ethics and social cohesion, were part of the ideas of most of these speeches. It was, therefore, a prospective view about society, creating the expectation that life in society could be improved by the use of appropriate instruments through the mediation of the educational system, which, finally, should excel in a directive practice to achieve a certain end. In this perspective, the idea of ​​Education that shaped Western society has always had a look towards the future, for the insertion of children and young people in society until the conclusion of this process when they are fully integrated when they reach adulthood. Undoubtedly, it was a teleological perspective of Man, where the beginning, middle and end were, in a certain way, determined from previously drawn parameters. However, it was not a closed scheme, where there would be no space for any differentiation in its interior. It could be said that this vision of Education, which lasted throughout the eighteenth and nineteenth centuries, served as a reference for educational practice that also had a relatively wide space for maneuver and flexibility. It was a consistent discussion and, despite a search for understanding a given totality, it could not be defined as totalitarian. The explicit purpose was to form free, autonomous and politically and economically emancipated men, preserving individual freedom and legal equality for all under the law. In other words, respect for the rule of law and citizenship. However, this perspective, essentially liberal, hid innumerable aspects in the social, political and economic spheres that ended up splashing, also, in the speeches about Education. Issues such as social inequality, conflicts between classes, the preservation of privileges, were not part of liberal discussions. Such aspects were, in the liberal view, an exception and not the rule for a society whose base was based much more on inequality than on freedom.